Faktor-Faktor yang Mempengaruhi Tingkat Persepsi Petani Terhadap Keberlanjutan Lahan Pertanian Pangan di Pinggiran Kota Pekalongan: Pendekatan Model Regresi Binary Probit - Imade Yoga Prasada (Journal of Data Science Theory and Application, 2024)
The sustainability of agricultural land on the outskirts of Pekalongan City will depend on the level of farmers' perception of the sustainability of agricultural land on the outskirts of Pekalongan City. A higher level of perception will have an impact on increasing the sustainability of agricultural land on the outskirts of Pekalongan City and vice versa. Therefore, this research was conducted to determine the factors that influence the level of farmers' perception of the sustainability of agricultural land on the outskirts of Pekalongan City. The data in this research is primary data taken from in-depth interviews with farmers on the outskirts of Pekalongan City. The research location was taken using the purposive sampling method. The total sample of research respondents was 90 farmer owners and cultivators and samples were taken using the simple random sampling method. Data were analyzed using a binary probit regression model. The research results show that the factors that influence the level of farmers' perception of the sustainability of agricultural land on the outskirts of Pekalongan City are knowledge about agricultural activities, knowledge about the multifunctionality of agricultural land, and the extent of farmers' land holdings.